Inhibitory effects of novel green inhibitors on gas hydrate formation - Tang, Cuiping; Liang, Deqing (Chinese Journal of Chemical Engineering, 2019)
Natural gas hydrates easily form in pipelines, causing potential safety issues during oil and gas production and transportation. Injecting gas hydrate inhibitors is one of the most effective methods for preventing gas hydrate formation or aggregation. However, some thermodynamic hydrate inhibitors are toxic and harmful to the environment, whereas degradation of kinetic inhibitors is difficult. Therefore, environmentally friendly and easily biodegradable novel green inhibitors have been proposed and investigated. This paper provides a short but systematic review of the inhibitory performance of amino acids, antifreeze proteins, and ionic liquids. For different hydrate formation systems, the influences of the inhibitor type, structure, and concentration on the inhibitory effects are summarized. The mechanism of green inhibitors as kinetic inhibitors is also discussed. The progress described here will facilitate further developments of such green inhibitors for gas hydrate formation. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.